2023
DOI: 10.3390/diagnostics13050853
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Echocardiography Measurements Concordance and Findings Agreement: An Exploratory Study

Abstract: The professional association has already developed guidelines on the appropriate use of handheld ultrasound devices, especially in an emergency setting. Handheld ultrasound devices are seen as the ‘stethoscope of the future’ to assist in physical examination. Our exploratory study evaluated whether the measurements of cardiovascular structures and the agreement in identifying aortic, mitral, and tricuspid valve pathology made by a resident with a handheld device (HH, Kosmos Torso-One) reach the results reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, owing to the universal applicability of the tele-HHUS system, we believe that it could play a key role in providing basic healthcare services for the public, especially in resource-limited settings [ 15 ]. Many studies have shown that as a new portable diagnostic tool, HHUS has the same diagnostic efficiency as conventional ultrasound in the diagnosis of diseases of the heart, liver, lungs, and other organs [ 5 , 16 , 17 , 18 ]. HHUS has unlimited diagnostic potential, especially in acute and critically ill patients [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, owing to the universal applicability of the tele-HHUS system, we believe that it could play a key role in providing basic healthcare services for the public, especially in resource-limited settings [ 15 ]. Many studies have shown that as a new portable diagnostic tool, HHUS has the same diagnostic efficiency as conventional ultrasound in the diagnosis of diseases of the heart, liver, lungs, and other organs [ 5 , 16 , 17 , 18 ]. HHUS has unlimited diagnostic potential, especially in acute and critically ill patients [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the dimension, the US examination had some advantages compared to other imaging techniques, such as lack of radiation, low cost, reproducibility, and the possibility to examine patients at point-of-care [56]. The trainees preferred a conventional high-end ultrasound device when available [29], while generally, the measurements were concordant [23,45,57], and the difficulty of US learning and comfort levels were similar (p > 0.15) [45].…”
Section: Rethinking Medical Educationmentioning
confidence: 97%
“…Ultrasound is a complex imaging modality, and image capturing and image interpretation require training [18,19], but there are still no standardized approaches regarding the content of training programs, their duration, or required trainer qualifications [20]. Considering that ultrasound examinations are user-dependent, the results reported in the scientific literature support the accuracy in measurements and lower image quality when compared to conventional US cardiac examinations [21][22][23].…”
Section: Introductionmentioning
confidence: 99%